Shoveling Smoke Advertising and Globalization in Contemporary India - Mazzarella, William (Duke University Press, 2003)
A leading Bombay advertising agency justifies as traditionally Indian the highly eroticized images it produces to promote the KamaSutra condom brand. Another agency struggles to reconcile the global ambitions of a cellular-phone service provider with the ambivalently local connotations of the client's corporate brand. When the dream of the 250 million-strong "Indian middle class" goes sour, Indian advertising and marketing professionals search for new ways to market "the Indian consumer"-now with added cultural difference-to multinational clients.An examination of the complex cultural politics of mass consumerism in a globalized marketplace, Shoveling Smoke is a pathbreaking and detailed ethnography of the contemporary Indian advertising industry. It is also a critical and innovative intervention into current theoretical debates on the intersection of consumerist globalization, aesthetic politics, and visual culture. William Mazzarella traces the rise in India during the 1980s of mass consumption as a self-consciously sensuous challenge to the austerities of state-led developmentalism. He shows how the decisive opening of Indian markets to foreign brands in the 1990s refigured established models of the relationship between the local and the global and, ironically, turned advertising professionals into custodians of cultural integrity